2019
DOI: 10.1093/jxb/erz523
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-box RNA helicase SHI2 functions in repression of salt-inducible genes and regulation of cold-inducible gene splicing

Abstract: Gene regulation is central for growth, development, and adaptation to environmental changes in all living organisms. Many genes are induced by environmental cues, and the expression of these inducible genes is often repressed under normal conditions. Here, we show that the SHINY2 (SHI2) gene is important for repressing salt-inducible genes and also plays a role in cold response. The shi2 mutant displayed hypersensitivity to cold, abscisic acid (ABA), and LiCl. Map-based cloning demonstrates that SHI2 encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The increased chilling sensitivity of the smeb mutants are restored by the hy5 mutation, indicating that HY5 may be involved in mediating chilling responses downstream of SmEb. Previous studies have shown that certain mutants with altered sensitivity to cold stress are involved in pre-mRNA splicing (Guan et al, 2013;Nakaminami & Seki, 2018;Wang et al, 2020;Zhu et al, 2020). In addition, the previously published mutants are defective in not only splicing but also other RNA processing events.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increased chilling sensitivity of the smeb mutants are restored by the hy5 mutation, indicating that HY5 may be involved in mediating chilling responses downstream of SmEb. Previous studies have shown that certain mutants with altered sensitivity to cold stress are involved in pre-mRNA splicing (Guan et al, 2013;Nakaminami & Seki, 2018;Wang et al, 2020;Zhu et al, 2020). In addition, the previously published mutants are defective in not only splicing but also other RNA processing events.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that certain mutants with altered sensitivity to cold stress are involved in pre‐mRNA splicing (Guan et al, 2013; Nakaminami & Seki, 2018; Wang et al, 2020; Zhu et al, 2020). In addition, the previously published mutants are defective in not only splicing but also other RNA processing events.…”
Section: Discussionmentioning
confidence: 99%
“…An RNA-Seq of A. thaliana plants from NaCl-treated seeds disclosed that 49% of genes with introns underwent splicing alterations, with 10% undergoing differential alternative splicing (SAD) [ 83 ]. In addition, after salinity exposure, plants of Gossypium davidsonii exhibited a significant increase (32%) in genes undergoing splicing alterations [ 84 ], while a crucial role in the stress response was played particularly by the SHI2 gene, with its DEAD-box activity in splicing cold response genes [ 85 ]. Another distinct cluster highlighted the biosynthesis of histidine, an amino acid crucial for plant growth, development, and responses to environmental factors, including salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the results suggested that AtRH7 affects rRNA biogenesis and plays an important role in plant growth under cold stress (Yuelin Liu, 2016). Wang reported that SHINY2 encodes a DEAD-(Asp-Glu-Ala-Asp) box RNA helicase that serves as a splicing factor required for proper splicing of cold-responsive genes (Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%